Investigation of the Physical Properties of Different Ion Species at Hadron Therapy; A Comprehensive Study - Ahmad Esmaili Torshabi (Frontiers in Biomedical Technologies)
Purpose: Recently, using hadrons as a therapeutic beam has been highly advised for radiation treatment of mainly deep-seated tumors due to the desired conforming of three-dimensional dose conformation onto tumor volume. This refers to the physical properties of commonly available hadrons versus photons and electrons in colliding with patient body atoms which is our main challenge in this study, in a comparative fashion.